Probability theory and application of item response theory - Md. Desa, Zairul Nor Deana; Abdul Latif, Adibah (Penerbit UTM Press, 2008)
Since 19705 item response theory became the dominant area for study by measurement specialist in education industry. The common models and procedures for constructing test and interpreting test scores served the measurement special ist and other test users well for a long time. In this paper, a number of assumptions about the classical test theory arc discussed. In addition, the contemporary test theory that is item response theory (lRT) will be discussed in general. There are tour strong assumptions about the probability theory of item response theory such as the dimensionality of the latent space. local independence theory. the item characteristics curves and the speededncss of the test. Furthermore. this discussion aimed to assist departments of education in considering the IRT that contributed in introducing the use of computerized adaptivc testing (CAT) as they move to transition testing programs to online in the future.